Effect of eicosapentaenoic acids-rich fish oil supplementation on motor nerve function after eccentric contractions - Eisuke Ochi; Yosuke Tsuchiya; Kenichi Yanagimoto (Taylor & Francis Group, 2017)
Background This study investigated the effect of supplementation with fish oil rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on the M-wave latency of biceps brachii and muscle damage after a single session of maximal elbow flexor eccentric contractions (ECC). Methods Twenty-one men were completed the randomized, double-blind, placebo-controlled, and parallel-design study. The subjects were randomly assigned to the fish oil group (n = 10) or control group (n = 11). The fish oil group consumed eight 300-mg EPA-rich fish oil softgel capsules (containing, in total, 600 mg EPA and 260 mg DHA) per day for 8 weeks before the exercise, and continued this for a further 5 days. The control group consumed an equivalent number of placebo capsules. The subjects performed six sets of ten eccentric contractions of the elbow flexors using a dumbbell set at 40% of their one repetition maximum. M-wave latency was assessed as the time taken from electrical stimulation applied to Erb's point to the onset of M-wave of the biceps brachii. This was measured before and immediately after exercise, and then after 1, 2, 3, and 5 days. Changes in maximal voluntary isometric contraction (MVC) torque, range of motion (ROM), upper arm circumference, and delayed onset muscle soreness (DOMS) were assessed at the same time points. Results Compared with the control group, M-wave latency was significantly shorter in the fish oil group immediately after exercise (p = 0.040), MVC torque was significantly higher at 1 day after exercise (p = 0.049), ROM was significantly greater at post and 2 days after exercise (post; p = 0.006, day 2; p = 0.014), and there was significantly less delayed onset muscle soreness at 1 and 2 days after exercise (day 1; p = 0.049, day 2; p = 0.023). Conclusion Eight weeks of EPA and DHA supplementation may play a protective role against motor nerve function and may attenuate muscle damage after eccentric contractions. Trial registration This trial was registered on July 14th 2015 (https://upload.umin.ac.jp/cgi-open-bin/ctr/index.cgi).